Antithrombotic therapy and cavernoma bleeding: does vascular border zone localization matter? - Alexandru Guranda; Tim Wende; Martin Vychopen; Erdem Güresir; Ulf Nestler (Frontiers in Surgery)
ObjectiveHemorrhagic events in cavernous malformations (CCMs) are linked to significant morbidity and mortality. Identifying factors contributing to bleeding is crucial for effective clinical and surgical management.MethodsThis retrospective, observational, single-center study assessed potential and known risk factors for bleeding in patients with cerebral cavernous malformations. We evaluated age, gender, smoking habits, arterial hypertension, antithrombotic medication, diabetes mellitus, cavernoma shape, size changes observed in follow-up MRIs, the occurrence of epileptic seizures, and the localization of the lesion in regard of cerebral vascular territories.ResultsWe identified 143 patients (43.4% male, 45.5% with hemorrhagic events, and 19.6% with epileptic seizures). Antithrombotic medication was associated with a lower frequency of hemorrhage (p = 0.012). Arterial hypertension, diabetes mellitus, smoking habits and localization in the border zone of a vascular territory or seizures were not significantly associated with bleeding events. An increased rate of hemorrhagic events was found in cavernomas with irregular MRI shape (p = 0.001), or with changes in size during follow-up (p = 0.012). Multivariate analysis confirmed that antithrombotic therapy was associated with a reduced risk of hemorrhage (OR: 0.151, 95% CI: 0.041–0.552, p = 0.004), while male gender (OR: 2.114, 95% CI: 1.047–4.269, p = 0.037), irregular cavernoma shape (p = 0.001), and cavernoma growth (p = 0.002) were independently associated with a higher bleeding risk. Cavernoma localisation in the border zone between median and posterior arterial territories was associated with a significant lower rate of bleeding events compared to localisation in other watershed areas.ConclusionWe observed a reduced percentage of bleeding in cavernoma patients utilizing antithrombotic agents, compared to patients without antithrombotic medication. Factors such as smoking habits, irregular cavernoma shape on MRI, and changes in size during follow-up were associated with a higher frequency of bleeding events.